Phylogenomic reappraisal of the family Rhizobiaceae at the genus and species levels, including the description of Ectorhizobium quercum gen. nov., sp. nov. - Ma, Tengfei; Xue, Han; Piao, Chungen; Jiang, Ning; Li, Yong (Frontiers in Microbiology, 2023)
The family Rhizobiaceae contains 19 validly described genera including the rhizobia groups, many of which are important nitrogen-fixing bacteria. Early classification of Rhizobiaceae relied heavily on the poorly resolved 16S rRNA genes and resulted in several taxonomic conflicts. Although several recent studies illustrated the taxonomic status of many members in the family Rhizobiaceae, several para- and polyphyletic genera still needed to be elucidated. The rapidly increasing number of genomes in Rhizobiaceae has allowed for a revision of the taxonomic identities of members in Rhizobiaceae. In this study, we performed analyses of genome-based phylogeny and phylogenomic metrics to review the relationships of 155-type strains within the family Rhizobiaceae. The UBCG and concatenated protein phylogenetic trees, constructed based on 92 core genes and concatenated alignment of 170 single-copy orthologous proteins, demonstrated that the taxonomic inconsistencies should be assigned to eight novel genera, and 22 species should be recombined. All these reclassifications were also confirmed by pairwise cpAAI values, which separated genera within the family Rhizobiaceae with a demarcation threshold of ~86%. In addition, along with the phenotypic and chemotaxonomic analyses, a novel strain BDR2-2T belonging to a novel genus of the family Rhizobiaceae was also confirmed, for which the name Ectorhizobium quercum gen. nov., sp. nov. was proposed. The type strain is BDR2-2T (=CFCC 16492T = LMG 31717T).